Validating impact of pretreatment tumor growth rate on outcome of early‐stage lung cancer treated with stereotactic body radiation therapy. Issue 2 (30th November 2020) - Atallah, Soha; Le, Lisa W.; Bezjak, Andrea; MacRae, Robert; Hope, Andrew J.; Pantarotto, Jason
Abstract : Background: To assess correlation of pretreatment specific growth rate (SGR) value of 0.43 × 10 ‐2 with overall and failure‐free survival of patients with early‐stage non‐small cell lung cancer (NSCLC) treated with stereotactic body radiation therapy (SBRT). Methods: A retrospective chart review of 160 patients with pathologically confirmed stage I NSCLC treated with SBRT between June 2010 and December 2012 in a large, tertiary cancer institute was undertaken. Both diagnostic and archived planning CT were uploaded to the treatment planning system to determine tumor volume at diagnosis (GTV1) and planning time (GTV2). The time (t) between both CTs was recorded. SGR was calculated using GTV1, GTV2, and t. The median SGR (0.43 × 10 ‐2 ) from our previous data was used to group patients into low and high SGR cohorts. Log‐rank test was used to compare overall (OS) and failure‐free survivals (FFS) of SGR groups. Results: The median time interval between diagnostic and planning CT scans was 87 days. The median OS was 38 and 66 months for high and low SGR cohorts, respectively ( P = 0.03). The median FFS was 27 and 55 months for high and low SGR cohorts, respectively ( P = 0.005). High SGR ( P  < 0.05), male gender ( P = <0.01), and GTV2 ( P = <0.05) were associated with poorer FFS. Conclusions: High SGR was associated with poorer outcome in patients with early‐stage NSCLC treated with SBRT. SGR can be used in conjunction with other well‐known predictive factors to formulate a practical predictive model to identify subgroups of the patient at higher risk of recurrence after SBRT. Abstract : We demonstrated that tumor growth rate (GR) predicts treatment outcome in early‐stage lung cancer patients treated with SBRT. We used specific growth rate (SGR) as a metric for pretreatment GR and its median (0.43 × 10 ‐2 ) to group patients into high and low SGR cohorts. In this study, the same median SGR was validated in an independent dataset at a different cancer institution. Patients with high SGR tumors consistently had significantly lower survival and higher regional failure.